Between Tradition and Revolution - Huong, Ngo Thi Minh (University of Jember, 2024)
Over the past century, the trajectory of gender equality in Vietnam has been marked by a nuanced interplay of historical contexts, societal norms, and ideological shifts. A burgeoning women’s movement has emerged, favoring the term ‘gender equality’ over ‘feminism’ in private and public spheres. Gender equality has historically challenged traditional norms, notably during times of war, reshaping gender roles. Under communism, gender equality became static, confining feminism within a framework of patriotism and heroism. The persistence of gender equality is revealed in the context of a complex and contested amalgam of Western feminist ideas and historical antecedents. This article delves into the evolution of gender roles in Vietnam, exploring how communism and wartime conditions influenced feminism from the national liberation era to the Vietnam War. The article argues that the patriarchal structure present in a longstanding culture of Confucianism in Vietnam does not inherently obstruct gender equality and women's rights. Instead, it stems from changing women’s roles outside the domestic sphere to heroism during war efforts. Vietnamese women’s movement, before the term ‘gender equality,’ emerged during wartime but did not contest feminism. The notion of gender equality has become static; however, feminism is still contested and has yet to be imported to this day. Keywords: Feminism, Gender Equality, War, Communism, Vietnam.